2012
DOI: 10.1590/s1517-86922012000200013
|View full text |Cite
|
Sign up to set email alerts
|

Uso do exercício resistido antagonizado por naloxone como fator de analgesia em sinovite aguda de joelho de ratos Wistar

Abstract: Analgesia arising from exercising can occur via release of endogenous opioids in the central nervous system and periphery. However, the literature remains controversial about exercise ways and actions in pain. Thus, the aim of this study was to evaluate whether resistance exercise produces changes on the nociception and suffers interference by applying an opioid inhibitor. 18 rats divided into three groups were used: G1 -hyperalgesia on right knee and untreated; G2 -hyperalgesia and treated with jump sin water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
3
0
2
Order By: Relevance
“…In these studies, the rats performed resistance exercises in water with a load attached to their body. The authors found a control of allodynia induced by formalin injected into the knee joint or calcaneal tendon trauma ( Antunes et al, 2012 ; Bertolini et al, 2012 ). Clinical studies have also demonstrated that resistance exercise relieves pain in fibromyalgia patients ( Jones, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the rats performed resistance exercises in water with a load attached to their body. The authors found a control of allodynia induced by formalin injected into the knee joint or calcaneal tendon trauma ( Antunes et al, 2012 ; Bertolini et al, 2012 ). Clinical studies have also demonstrated that resistance exercise relieves pain in fibromyalgia patients ( Jones, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported the efficiency of non-pharmacological treatment strategies against muscle injuries, among which resistance exercise training has been proven beneficial to control pain ( Bertolini et al, 2012 ; Galdino et al, 2014 ; Jones, 2015 ). In addition to resistance exercise training, the ingestion of supplements, such as whey protein, may attenuate muscle microinjuries, pain, and local macrophage infiltration caused by some muscular stress resulting from exercise and cryolesion ( Pereira et al, 2014 ; Kato et al, 2016 ; Qin et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, in the present study, we began the treatment with swimming exercise in the 3rd PO, during which the changes arising from nerve compression had already been established. It was realized that the aquatic exercise could be important in recovering from paresis, both by decreasing the protein degradation 21 and by functioning as a possible analgesia mediated by endogenous opioids, 22 which could reduce the immobility of the limb due to pain. When a peripheral nerve suffers compression (inducing local ischemia), some electrophysiological nerve conduction change occurs, 23 leading to muscle weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Sendo assim, no presente estudo iniciou-se o tratamento com natação no terceiro dia PO, período em que as alteraç ões decorrentes da compressão nervosa já haviam se instalado. Vislumbrou-se que o exercício em meio aquático poderia ser importante na recuperação da paresia, tanto pela diminuição da degradação proteica 21 quanto por uma possível analgesia mediada por opioides endógenos, 22 o que poderia reduzir o imobilismo do membro devido à dor. Quando os nervos periféricos sofrem compressões que induzem a isquemia local ocorrem alteraç ões eletrofisiológicas na condução nervosa, 23 o que gera a fraqueza muscular.…”
Section: Discussionunclassified